Associations of scoring accuracy with postural stability and strength measures in archers on a standard archery site - Fan, C.-H.; Liao, C.-N.; Hsu, W.-H. (Sports, 2025)
Archery performance is substantially influenced by postural stability. Although archery is commonly practiced outdoors, most studies have focused on short-distance indoor environments. Accordingly, this study examined the correlation between postural stability and shooting accuracy in competitive recurve and compound archers on a standard outdoor field (70 m for recurve and 50 m for compound). This study included 37 archers. Each archer`s performance was recorded during a simulated competition. Measurements included muscle strength, body stability, and center of pressure. Postural stability data were analyzed at 0.5 s before and 0.1 s after arrow release. The results indicated that compared with compound archers, recurve archers had stronger upper-limb muscles and exhibited lower pre-release total center of pressure (51.9 mm; p = 0.022) and medial/lateral sway (1.1 mm; p = 0.043). The compound archers exhibited lower post-release anterior/posterior sway (3.2 mm; p = 0.001) and lower angular velocities in most body segments, except for the lower back. The recurve archers relied more on post-release stability, whereas the compound archers relied more on pre-release control. Linear regression analysis identified different predictors of scoring accuracy for each bow type. Our findings highlight the need for discipline-specific training strategies, such as enhancing bow-side stability for recurve archers and drawing-side control for compound archers.